2005
DOI: 10.1002/ijc.20982
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant adeno‐associated virus‐mediated TRAIL gene therapy suppresses liver metastatic tumors

Abstract: To evaluate the tumoricidal activity of tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) on disseminated liver metastatic tumors, we constructed a recombinant adenoassociated virus (rAAV) expressing the extracellular domain (95-281aa) of human TRAIL (TRAIL , and the recombinant virus was designated as rAAV-TRAIL) using the 3-plasmid, helper-virus-free, packaging system. Transduction of mouse lymphoma EL-4 cells and Jurkat T cells lead to the expression of TRAIL 95-281 protein in both viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 24 publications
(44 reference statements)
2
37
2
Order By: Relevance
“…Infectious AAV particles were generated in human embryo kidney cells with packaging-helper plasmid pDG 12 and purified via heparin affinity chromatography as previously described. 9 The recombinant virus titers were determined by measuring the copy number of viral genomes in pooled, dialyzed gradient fractions using a real-time PCR (RT-PCR) procedure with primers of the WPRE enhancer region. The standard titer was determined via preexperiment of SMMC-7721 cells transduced with AAVenhanced green fluorescent protein (EGFP).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Infectious AAV particles were generated in human embryo kidney cells with packaging-helper plasmid pDG 12 and purified via heparin affinity chromatography as previously described. 9 The recombinant virus titers were determined by measuring the copy number of viral genomes in pooled, dialyzed gradient fractions using a real-time PCR (RT-PCR) procedure with primers of the WPRE enhancer region. The standard titer was determined via preexperiment of SMMC-7721 cells transduced with AAVenhanced green fluorescent protein (EGFP).…”
Section: Methodsmentioning
confidence: 99%
“…cDNA was prepared via reverse transcriptional PCR as previously described. 9 The relatively quantitative PCR reaction was set up in a total volume of 20 L containing 2 L of diluted cDNA, 10 L of 2ϫ SYBR Green PCR mix buffer (ABI, Foster City, CA), and 1 mol/L of each primer. RT-PCR was performed by using WPRE primers 5Ј-TGGCGTGGTGTGCACTGT-3Ј and 5 Ј-GTTCCGCCGTGGCAATAG-3Ј and ␤-actin primers 5Ј-ATGGTGGGAATGGGTCAGAAG-3Ј and 5Ј-CACGCAGCTCATTGTA GAAGG-3Ј on Applied Biosystems 7500 (ABI) at 50°C for 2 minutes, 95°C for 10 minutes, and 40 cycles of 95°C for 15 seconds and 60°C for 1 minute.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously established a recombinant AAV-mediated soluble TRAIL 95-281 gene expression for cancer therapy 25,26 and demonstrated that intraportal injection via the hepatic portal veins of rAAV-TRAIL 95-281 into the liver of an orthotopic-transplanted EL-4 mouse model mimicking liver cancer metastasis resulted in a significant suppression of tumor growth and prolonged survival, while normal hepatocyte toxicity is undetectable. Histological and biochemical analysis in tumor tissue and serum confirmed that TRAIL 95-281 in active trimeric form was stably expressed in relatively high level in hepatocytes and secreted into the serum.…”
Section: Introductionmentioning
confidence: 99%